Serum separation abnormality in a multiple myeloma patient - Zaharudin, Mohd Radzli; Thambiah, Subashini C.; Samsudin, Intan Nureslyna; A. Hamid, Hanisah (Malaysian Society of Pathologists, 2023)
Introduction: M-protein secreted by myeloma cells do not only contribute to myeloma-related complications but is also a well-recognised source of interference in laboratory assays. We describe a case of a 62-year-old woman whose blood sample showed improper serum separation even after resampling. Case report: Centrifugation of a biochemistry specimen in a serum-separator tube received by the laboratory failed to separate any serum, nor did repeating the process at a longer duration. Repeat sampling only yielded a small volume of serum from which highly elevated total protein was noted upon analysis. Additional history from the treating clinician unveiled a diagnosis of multiple myeloma in this patient. Discussion: This case represents one of the rare, but significant pre-analytical interferences caused by M-proteins.